Criminal Justice and Public Opinion in Italy between the Nineteenth and Twentieth Centuries - Luigi Lacchè (Revista Brasileira de Direito Processual Penal, 2021)
Through the Italian example – but also with references to the experience of the formation of the so-called "mixed system" in France and the experience of Great Britain, seen as a model for continental reformers – the present article aims to demonstrate that "modern criminal justice" is characterized from its origin by the – problematic – link between criminal justice and public opinion. At first, despite some perplexities, publicity is seen as an indelible feature of criminal justice in a liberal regime. In a second moment, publicity is attacked – by scuola positiva jurists, for example – as something incompatible with the scientificity of the judicial process, until publicity itself would lose its original meaning with the advent of fascism.